Supply Function Equilibria in Oligopoly under Uncertainty - Klemperer, Paul D.; Meyer, Margaret A. (Econometrica, 1989)
The authors model an oligopoly facing uncertain demand where each firm chooses as its strategy a "supply function" relating its quantity to its price. A supply function adapts better to an uncertain environment than either a fixed price or a fixed quantity; it could be committed to through the choice of organizational structure and employee decision rules. The authors give conditions for existence and for uniqueness of a Nash equilibrium in supply functions under uncertainty. They compare the equilibrium with the Cournot and Bertrand equilibria as they vary the demand and cost curves, the number of firms, and the form of uncertainty.